ANALYSIS THE CONSTRUCTION MANAGEMENT ANALYSIS OF THE KARAWANG GOVERNMENT OFFICE - Hangger Muhammad Ma’rifatullah; Fathur Rohman (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2018)
The purpose of this thesis is to know volume of work on construction of Karawang Government Office Project, analyze method of implementation of work, to know the cost of implementation on construction of Karawang Government Office Project, and the comparison of time duration between scheduling prediction of owner with scheduling prediction of author. This type of the research is quantitative. That describes the condition of a particular project with existing data related to the construction of local government buildings. That existing data is processed in such a way as to produce the final conclusion. The result of the research is Based on Budget Cost calculations to complete Karawang government office construction until the final stage, more or less costly Rp.41.906.713.365,-. From the calculation of weight of work is estimated completion of Karawang government office construction work takes 75 weeks. With the CPM method can be known critical path occurs in the project are Excavation and Pile Up Work – Pile Foundation Work – River Stone Foundation Work – Reinforced Concrete Work – Wall, Brick, and Plastering Work – Door Frame, Leaf Door, and Window Work - Ceiling Work – Sanitation Set Work - Lighting Installation Work – Lift Work. Keyword : Construction Management, Barchart, S Curve, Critical Path.